A simulation model for the long-term analysis of decentralized electricity markets - Paşaoğlu, Güzay. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2006., 2006)
After the liberalization of the electricity generation industry, capacity expansion decisions are made by multiple self-oriented power companies. Unlike the regulated environment, decision-making of market participants is now guided by price signal feedbacks and by an imperfect foresight of the future market conditions that they will face. In such an environment, decision makers need to understand long-term dynamics of the supply and demand sides of the power market. To visualize the competitive electricity power market dynamics, a simulation model based on system dynamics (SD) philosophy is developed in this study. The developed model includes the demand module, the capacity expansion module, the power generation sector, an accounting and financial module, various competitors and a bidding mechanism. During the modeling process, various submodels have been developed and tested before being integrated to form a complete system model. At each phase of modeling, besides international literature, expert opinions have been considered in determining the model structure, relationship between entities, parameters and equations used in the model, to ensure the representativeness and the reliability of the model. In this context, additionally an Analythical Hierarchical Process based sub modeling and analysis has been conducted, in order to better understand and treat power generation facility options available to investors. The SD model has a flexible structure for parametric studies, such that results of different strategies/policies can be analyzed. The results obtained from the scenario analysis reveal that the model is able to capture most of the long and short-term dynamics which occur both on the supply and on the demand sides of the power market. The developed model is an excellent tool to be used in understanding, investigating and experimenting on a decentralized electricity market, especially in regard to investor behaviour; supply, demand and price fluctuations, short and long term effects of various decisions and primary energy resource limitations.
Keywords: Electric power distribution.; Electric power system stability.; Decision making -- Mathematical models.